Pengaruh Arus Kas Operasi, Laba Akuntansi, Current Ratio, Total Asset Trunover Terhadap Return Saham Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020 - Nelly Nattasyah Sagala; Deasy Arisandi Aruan; Jefry Sumonang Hendrikus Situmorang; Eben Ezer Sinaga (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to understand the effect of operating cash flow, accounting profit, current ratio, total asset turnover onstock returns in consumer goods industry companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study uses a purposive sampling method with a population of 53 companies in the consumer goods industry sector listed on the Indonesian stock exchange for the 2017-2020 period. The research sample is 120 companies in the consumer goods industry sector listed on the Indonesian stock exchange for the 2017-2020 period. The data investigation method used is multiple linear regression. The results of this study partially indicate that the Accounting Profit variable has a significant effect on Stock Return, but Operating Cash Flow, Current Ratio and Total Asset Trunover have no significant effect on Stock Return. Simultaneously operating cash flow, accounting profit, current ratio and total asset turnover have a significant effect on stock returns in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Keywords: Operating Cash Flow, Accounting Profit, Current Ratio, Total Asset Trunover, Stock Return.